Proceedings of the 1992 ACM SIGMOD International Conference on Management of Data 1992
DOI: 10.1145/130283.130300
|View full text |Cite
|
Sign up to set email alerts
|

Event specification in an active object-oriented database

Abstract: The concept of a trigger is centrrd to any active database. Upon the occurrence of a trigger even~the trigger is "fired", i.e, the trigger action is executed. We describe a model and a language for specifying basic and composite trigger events in the context of an object-oriented database. The specified events can be detected efficiently using finite automata. We integrate our model with O++, the database programming language for the Ode object database being developed at AT&T Bell Labs. We propose a new Event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(42 citation statements)
references
References 9 publications
0
40
0
1
Order By: Relevance
“…Much work has been done in active database systems on composite event detection [7,14,15], and a comprehensive study of the semantics of composite events can be found in [24]. Among the work, basic methods such as tree-based approach [7], Petri Nets model [14] and finite automata [15] have been proposed.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Much work has been done in active database systems on composite event detection [7,14,15], and a comprehensive study of the semantics of composite events can be found in [24]. Among the work, basic methods such as tree-based approach [7], Petri Nets model [14] and finite automata [15] have been proposed.…”
Section: Related Workmentioning
confidence: 99%
“…Among the work, basic methods such as tree-based approach [7], Petri Nets model [14] and finite automata [15] have been proposed. But, as noted in [19], arbitrary tree plans in Snoop [7] may suffer from poor performance; Petri Nets are too complicated to put into practice use; and concurrent relationships are not supported in Ode [15].…”
Section: Related Workmentioning
confidence: 99%
“…In the Ode object database [6], composite events are specified with a regularexpression-like language and detected using finite state automata (FSA). Equivalence between the CE language and regular expressions is shown.…”
Section: Related Workmentioning
confidence: 99%
“…The event based paradigm has gathered momentum as witnessed by current efforts in areas including event driven architectures, complex event processing, business process management and modeling, grid computing, web services notifications, event stream processing, and message-oriented middleware [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][21][22][23][24][25][26]. The increasing popularity of event based systems has opened new challenging issues for event based systems.…”
Section: Introductionmentioning
confidence: 99%